Case Report: Abdominal surgery with the support of Impella (SURGELLA), a new frontier to be explored - Guarracini, Stefano; Di Sebastiano, Pierluigi; Di Mola, Fabio Francesco; Di Renzo, Raffaella; Mazzocchetti, Lorenzo; Calafiore, Antonio M.; Di Mauro, Michele (Frontiers in Cardiovascular Medicine, 2024)
A 74-year-old man with advanced heart failure was admitted with a diagnosis of colorectal cancer and underwent surgery. To maintain stable hemodynamics Impella-CP was used. The patient was weaned from the device shortly after surgery and had an uneventful postoperative course. This case may pave the way for non-procrastinating surgery in patients with poorly stable hemodynamics.